Intensity and Unpleasantness of Pain Following Vaginal and Cesarean Delivery: A Prospective Evaluation. Issue 2 (14th June 2013) - Hardy‐Fairbanks, Abbey J.; Lauria, Michele R.; Mackenzie, Todd; Mccarthy, Martin
Abstract Background To date, most studies evaluating pain associated with cesarean birth have focused on delivery procedures or postoperative pain control methods rather than on the nature or severity of the pain experience of women, despite the increasing incidence and maternal requests for cesarean delivery. The objective in this study was to evaluate sensory, affective, and laterality aspects of pain after cesarean delivery and vaginal delivery. Methods A prospective cohort study using a seven‐item visual analog scale assessed pain at rest and with activity, and the unpleasantness and location of pain on postpartum days 1 and 2. Chart review identified demographic and clinical factors influencing pain. Multivariable regression and propensity score analyses were used to evaluate patient‐level outcomes. Results Of 126 consenting women, 48 underwent cesarean delivery and 78 had vaginal delivery. No statistically significant differences in pain at rest and pain unpleasantness were found between groups on postpartum day 1, but women undergoing cesarean delivery reported more pain with activity than those who had a vaginal delivery (p < 0.0002). On postpartum day 2, cesarean delivery women reported significantly more pain when compared with those with a vaginal delivery (p < 0.04), and more cesarean delivery women reported lateralized pain (p < 0.0001). In multivariate regression analyses, cesarean delivery was the most significant predictor of activity‐related pain on postpartum day 1 (p < 0.00001), followed by current substance abuse (p < 0.01). Women undergoing cesarean delivery required twice the dosage of analgesics on postpartum day 1 and four times greater amounts on postpartum day 2 relative to those with a vaginal delivery (p < 0.01 and p < 0.001). Conclusions Cesarean delivery was associated with higher levels of pain, more unpleasant pain, more lateralized pain, and greater narcotic use than vaginal delivery. Evaluation of factors associated with postpartum pain can help practitioners to counsel women better about their delivery alternatives and can promote improved management of women undergoing both types of delivery experiences (BIRTH 40:2 June 2013).